Circadian Rhythms, Melatonin and Depression - A. Quera Salva, M.; Hartley, S.; Barbot, F.; C. Alvarez, J.; Lofaso, F.; Guilleminault, C. (Current Pharmaceutical Design, 2011)
The master biological clock situated in the suprachiasmatic nuclei of the anterior hypothalamus plays a vital role in orchestrating the circadian rhythms of multiple biological processes. Increasing evidence points to a role of the biological clock in the development of depression. In seasonal depression and in bipolar disorders it seems likely that the circadian system plays a vital role in the genesis of the disorder. For major unipolar depressive disorder (MDD) available data suggest a primary involvement of the circadian system but further and larger studies are necessary to conclude. Melatonin and melatonin agonists have chronobiotic effects, which mean that they can readjust the circadian system. Seasonal affective disorders and mood disturbances caused by circadian malfunction are theoretically treatable by manipulating the circadian system using chronobiotic drugs, chronotherapy or bright light therapy. In MDD, melatonin alone has no antidepressant action but novel melatoninergic compounds demonstrate antidepressant properties. Of these, the most advanced is the novel melatonin agonist agomelatine, which combines joint MT1 and MT2 agonism with 5-HT2C receptor antagonism. Adding a chronobiotic effect to the inhibition of 5-HT2C receptors may explain the rapid impact of agomelatine on depression, since studies showed that agomelatine had an early impact on sleep quality and alertness at awakening. Further studies are necessary in order to better characterize the effect of agomelatine and other novel melatoninergic drugs on the circadian system of MDD patients. In summary, antidepressants with intrinsic chronobiotic properties offer a novel approach to treatment of depression.
Keywords: hypersomia